Genetic dissection of a TIR‐NB‐LRR locus from the wild North American grapevine species Muscadinia rotundifolia identifies paralogous genes conferring resistance to major fungal and oomycete pathogens in cultivated grapevine. (17th October 2013) - Feechan, Angela; Anderson, Claire; Torregrosa, Laurent; Jermakow, Angelica; Mestre, Pere; Wiedemann‐Merdinoglu, Sabine; Merdinoglu, Didier; Walker, Amanda R.; Cadle‐Davidson, Lance; Reisch, Bruce; Aubourg, Sebastien; Bentahar, Nadia; et al.
Summary: The most economically important diseases of grapevine cultivation worldwide are caused by the fungal pathogen powdery mildew ( Erysiphe necator syn. Uncinula necator ) and the oomycete pathogen downy mildew ( Plasmopara viticola ). Currently, grapegrowers rely heavily on the use of agrochemicals to minimize the potentially devastating impact of these pathogens on grape yield and quality. The wild North American grapevine species Muscadinia rotundifolia was recognized as early as 1889 to be resistant to both powdery and downy mildew. We have now mapped resistance to these two mildew pathogens in M. rotundifolia to a single locus on chromosome 12 that contains a family of seven TIR‐NB‐LRR genes. We further demonstrate that two highly homologous (86% amino acid identity) members of this gene family confer strong resistance to these unrelated pathogens following genetic transformation into susceptible Vitis vinifera winegrape cultivars. These two genes, designatedr esistance to U ncinulan ecator ( MrRUN1 ) andr esistance to P lasmoparav iticola ( MrRPV1 ) are the first resistance genes to be cloned from a grapevine species. Both MrRUN1 and MrRPV1 were found to confer resistance to multiple powdery and downy mildew isolates from France, North America and Australia; however, a single powdery mildew isolate collected from the south‐eastern region of North America, to which M. rotundifolia is native, was capable of breaking MrRUN1 ‐mediated resistance. Comparisons of gene organization and coding sequences between M. rotundifolia and the cultivated grapevine V. vinifera at the MrRUN1 / MrRPV1 locus revealed a high level of synteny, suggesting that the TIR‐NB‐LRR genes at this locus share a common ancestor.